Pengaruh CSR, Kepemilikan, Dividen & Profitabilitas terhadap Nilai Perusahaan Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia 2021-2024 - Rahmat Rinaldi; Novita Weningtyas Respati; Wahyudin Nor (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the effect of corporate social responsibility (CSR), managerial ownership, institutional ownership, independent board of commissioners, dividend policy, and profitability on firm value in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. A quantitative approach was used with multiple linear regression analysis. The sample consisted of 10 companies selected through purposive sampling, using secondary data from annual financial statements and sustainability reports. The results show that, partially, managerial ownership, independent commissioners, and profitability have a significant positive effect on firm value. Meanwhile, CSR, institutional ownership, and dividend policy do not have a significant effect. Simultaneously, all independent variables collectively influence firm value, with an adjusted R² value of 0.507, indicating that the model explains 50.7% of the variation in firm value. These findings suggest that internal governance mechanisms such as managerial shareholding, effective independent oversight, and the ability to generate profits play a more dominant role in determining firm value compared to CSR practices or dividend distribution. The implications of this study are expected to provide insights for management and stakeholders in improving firm value by strengthening ownership structure and profitability performance.